2004
DOI: 10.1136/ard.2003.008623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-citrullinated filaggrin antibodies as hallmarks for the diagnosis of rheumatic diseases

Abstract: Background: Anti-filaggrin antibodies (AFA) are among the most specific antibodies for rheumatoid arthritis, so procedures for their detection should be included in early biological diagnoses. AFA can be detected by indirect immunofluorescence (anti-keratin antibodies, AKA) or by new enzyme immunoassays (EIA). Their comparative performance needs to be established. Objective: To compare these technical procedures to optimise the serological diagnosis of rheumatoid arthritis. Methods: Results obtained using AKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 26 publications
8
44
1
6
Order By: Relevance
“…The anti-CCP positivity found among RA patients in the present study is in agreement with Dubucquoi et al (27), who reported a sensitivity of 85%. The anti-CCP2 test used in our study has higher sensitivity than the anti-CCP1 test (28).…”
Section: Discussionsupporting
confidence: 82%
“…The anti-CCP positivity found among RA patients in the present study is in agreement with Dubucquoi et al (27), who reported a sensitivity of 85%. The anti-CCP2 test used in our study has higher sensitivity than the anti-CCP1 test (28).…”
Section: Discussionsupporting
confidence: 82%
“…The report for sensitivity of the second [2] generation anti-CCP 2 antibody is approximately 64-74%, with the specificity of 90-99% [11][12][13][14][15][16]32]. The advantages of the use of anti-CCP 2 test might be seen as a possibility of an early differentiation of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest an important role of citrullinated antigens in the diagnosis of RA. Sensitivity of the anti-CCP 2 test varies between 64% and 74% in different populations, but the specificity varies between 90% and 99% [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dubucquoi et al compararon la positividad de anticuerpos anti-CCP en pacientes con AR en función de la linealidad del péptido citrulinado (34). El uso de péptidos citrulinados cíclicos mostró mejor sensibilidad y especificidad que los AKA y que el péptido citrulinado lineal (34). Igualmente, este estudio mostró una menor sensibilidad de los anticuerpos anti-CCP al inicio de la enfermedad que en pacientes con AR establecida (34).…”
Section: Discussionunclassified
“…Estudios previos señalaron una prevalencia de hasta el 20% en pacientes con LES (54) y del 4% en pacientes con SSp (34). Además del origen racial que pudiera explicar la diferencia entre los resultados, los criterios de selección de los pacientes deben ser también considerados en la interpretación de los mismos.…”
Section: Discussionunclassified